Shift in the larval phenology of a marine ectotherm due to ocean warming with consequences for larval transport. Issue 2 (26th October 2020) - McGeady, Ryan; Lordan, Colm; Power, Anne Marie
Abstract: Because environmental temperature has an important influence on developmental rate and physiology, marine ectotherms are vulnerable to phenology changes due to ocean warming. Identifying changes to phenology, the timing of biological events, and understanding their effect on recruitment and abundance is of critical importance to establish potential population effects. We examined the larval phenology of the commercially important Norway lobster ( Nephrops norvegicus ) and used a larval transport model to examine its effect on simulated transport patterns. Using a model to estimate annual larval release dates based on temperature‐dependent embryo incubation, an earlier shift of 17.2 d occurred between 1982–1995 and 2000–2010 in the Irish Sea, similar to an observed empirical shift in phenology of 19.1 d using historical zooplankton data sets. Despite this earlier phenology, temperature‐dependent pelagic larval durations were unchanged because the water column to which larvae were released earlier had also warmed. Larval transport simulations in the western Irish Sea indicated that the phenology shift had minimal effects on larval retention and advection distance overall, because major variations were observed only at very early or late stages of the larval season, that is, times when lower proportions of larvae were present. As the western Irish Sea grounds exports small but consistent quantities of larvae to nearby populations, especially off Scotland, it may act as an important source of larvae, especially when retention of native larvae is low. Overall, larval transport tools may indicate grounds that are periodically vulnerable to recruitment failures and offer potentially valuable information in fishery management.